2017
DOI: 10.5489/cuaj.4605
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of the recurrent renal stone former with current best practice guidelines

Abstract: Introduction: Patient compliance to best practice guidelines is a significant factor in preventing renal stone recurrence. While patient compliance has been historically poor, there remains a paucity of data in the renal stone setting. We evaluated compliance of the recurrent renal stone former with current Canadian Urological Association (CUA) best practice guidelines. Methods: A prospective, cross-sectional study design was used to evaluate patient compliance. Recurrent renal stone former patients were conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
2
7
0
1
Order By: Relevance
“…In addition, 67. 1% of patients believed in the efficacy of preventative stone measures and 22.8% of patients perceived their stone disease to be severe [21]. Dauw et al found an adherence rate of 30.3% with preventive pharmacologic therapy in kidney stone patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 67. 1% of patients believed in the efficacy of preventative stone measures and 22.8% of patients perceived their stone disease to be severe [21]. Dauw et al found an adherence rate of 30.3% with preventive pharmacologic therapy in kidney stone patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is of outmost importance because even adherence to these nonspecific measures, such as increased fluid intake, salt compliance, and citrate and protein intake is only 45.8%. 22 To the best of our knowledge only two studies were previously published in the literature, both by Dauw and colleagues 23,24 that examined nonadherence and the associated factors in patients with nephrolithiasis. Both studies were based on medical and pharmacy claims data.…”
Section: Discussionmentioning
confidence: 99%
“…Простая, на первый взгляд, рекомендация по повышению потребления воды на самом деле выполняется не всеми больными [68]. При этом сами больные могут быть уверены и/или уверять своего врача, что потребляют достаточно воды [69].…”
Section: итоги для клинической практикиunclassified